Audit from a Hemodialysis Facility in a small town in Punjab (Pakistan Journal of Kidney Diseases, 2024)
Patients with advanced Chronic Kidney Disease ultimately require Renal Replacement Therapy. In the absence of widespread availability of renal transplant, dialytic therapies remain the last court of appeal for most of the patients with CKD V. Hemodialysis remains the most common form of dialytic therapy utilized by the patients. Since the governmental support for dialysis has increased in the recent years, now the therapy is also available in smaller cities and towns. This is commendable since it reduces the financial burden of patients associated with travelling to larger cities twice a week to receive dialysis therapy. These centers in smaller towns have their own profile of problems to deal with. Here we present our data collected from hemodialysis centre in a small city of Pakistan.
Keywords: hemodialysis; hepatitis; vascualr access; arteriovenous fistula; temporary vascular catheter